1999
DOI: 10.1152/ajpregu.1999.276.6.r1825
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoids in the maturation of renal cortical Na+-K+-ATPase during fetal life in sheep

Abstract: Glucocorticoid levels increase greatly at the time of birth in humans and sheep, coinciding with an increased ability of the kidney to reabsorb sodium. Cortisol induces proximal tubule apical membrane Na+/H+exchanger maturation in near-term fetal sheep. Proximal tubule salt transport is ultimately dependent on Na+ pump activity, so we studied the effects of cortisol treatment on renal cortical Na+-K+-ATPase. We first looked at six 140 day gestation fetal sheep (term is 145) and compared their renal cortical Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…Another possible mechanism is that hypoxia may affect the expression of retinoid receptors that mediate remodeling process in epithelial cells associated with nephron genesis 35. Additionally, it has been shown that hypoxia increases the expression of glucocorticoid receptors in the primary human renal cortex epithelial cells 36, and that glucocorticoids play an important role in accelerating the maturation process of the kidney function 37, 38. Furthermore, the previous study demonstrated that hypoxia up-regulated the expression of angiopoietin-2 in cultured mouse kidney mesangial cells, which may have a synergistic paracrine role in the growth of glomerular endothelial during the development of the kidney 39.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is that hypoxia may affect the expression of retinoid receptors that mediate remodeling process in epithelial cells associated with nephron genesis 35. Additionally, it has been shown that hypoxia increases the expression of glucocorticoid receptors in the primary human renal cortex epithelial cells 36, and that glucocorticoids play an important role in accelerating the maturation process of the kidney function 37, 38. Furthermore, the previous study demonstrated that hypoxia up-regulated the expression of angiopoietin-2 in cultured mouse kidney mesangial cells, which may have a synergistic paracrine role in the growth of glomerular endothelial during the development of the kidney 39.…”
Section: Discussionmentioning
confidence: 99%
“…Avner et al (3) reported that HC-induced cyst formation in E13 mouse metanephroi was reduced by ouabain, a blocker of Na ϩ -K ϩ -ATPase. In fact, glucocorticoids induce Na ϩ -K ϩ -ATPase activity in rat isolated proximal tubule cells and whole kidneys in vivo (21,55), and in fetal sheep, they upregulate kidney levels of transcripts and proteins for the ␣ 1 -and ␤ 1 -subunits of Na ϩ -K ϩ -ATPase (44). These effects are mediated by enhancement of transcription of genes coding for these molecules (55), and indeed, Atp1a and Atp1b each have a putative GRE.…”
Section: Steroid-induced Growth Restriction Of the Developing Kidneymentioning
confidence: 99%
“…Because prenatal treatment with cortisol alters renal cortical Na ϩ -K ϩ -ATPase activity (91), inappropriate glucocorticoid exposure in utero may also lead to alterations in sodium transporters with subsequent effects on sodium and water balance leading to a reduction in pressure natriuresis and hypertension. Thus fetal exposure to inappropriate levels of glucocorticoids is associated with both structural and physiological alterations.…”
Section: R5 Fetal Programming Of Hypertensionmentioning
confidence: 99%